Extensive genomic characterization of a set of near-isogenic lines for heterotic QTL in maize (Zea mays L.) - Pea, Giorgio (BioMed Central, 2013)
BACKGROUND: Despite the crucial role that heterosis has played in crop improvement, its genetic and molecular bases are still elusive. Several types of structured populations were used to discover the genetic architecture underlying complex phenotypes, and several QTL related to heterosis were detected. However, such analyses generally lacked the statistical power required for the detailed characterization of individual QTL. Currently, QTL introgression into near-isogenic materials is considered the most effective strategy to this end, despite such materials inevitably contain a variable, unknown and undesired proportion of non-isogenic genome. An introgression program based on residual heterozygous lines allowed us to develop five pairs of maize (Zea mays L.) near-isogenic lines (NILs) suitable for the fine characterization of three major heterotic QTL previously detected. Here we describe the results of the detailed genomic characterization of these NILs that we undertook to establish their genotypic structure, to verify the presence of the expected genotypes within target QTL regions, and to determine the extent and location of residual non-isogenic genomic regions. RESULTS: The SNP genotyping approach allowed us to determine the parent-of-origin allele for 14,937 polymorphic SNPs and to describe in detail the genotypic structure of all NILs. The correct introgression was confirmed for all target QTL in the respective NIL and several non-isogenic regions were detected genome-wide. Possible linkage drag effects associated to the specific introgressed regions were observed. The extent and position of other non-isogenic regions varied among NIL pairs, probably deriving from random segregating sections still present at the separation of lineages within pairs. CONCLUSIONS: The results of this work strongly suggest that the actual isogenicity and the genotypic architecture of near-isogenic materials should be monitored both during the introgression procedure and on the final materials as a paramount requisite for a successful mendelization of target QTL. The information here gathered on the genotypic structure of NILs will be integrated in future experimental programs aimed at the fine mapping and isolation of major heterotic QTL, a crucial step towards the understanding of the molecular bases of heterosis in maize.